2021
DOI: 10.1111/jmi.13035
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical model and experimental study on environmental dissipation mechanism of tapping mode atomic force microscope

Abstract: The phase information reflects the energy dissipation of the probe and sample interactions in tapping mode atomic force microscopes (TM AFMs). In this paper, we use the method of tune test in TM AFM to study the contribution of external environment to energy dissipation by changing the probe position and ambient humidity. Finally, the theoretical and experimental quality factors of air viscous damping, squeeze film damping and liquid bridge force are obtained to characterise energy dissipation. The analyticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…where ๐‘š represents the equivalent mass of the microcantilever beam; ๐‘ represents the equivalent external damping that describes background dissipation; ๐‘˜ is the spring constant of the microcantilever beam; ๐‘ง represents the absolute displacement of the tip; and ๐‘ง represents the support excitation. A number of studies have now shown that the tip-sample contact stiffness is small and has little effect on the intrinsic frequency of the probe [5,16,17]. Therefore, the effect of ๐‘˜ can be neglected and Eq.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…where ๐‘š represents the equivalent mass of the microcantilever beam; ๐‘ represents the equivalent external damping that describes background dissipation; ๐‘˜ is the spring constant of the microcantilever beam; ๐‘ง represents the absolute displacement of the tip; and ๐‘ง represents the support excitation. A number of studies have now shown that the tip-sample contact stiffness is small and has little effect on the intrinsic frequency of the probe [5,16,17]. Therefore, the effect of ๐‘˜ can be neglected and Eq.…”
Section: Theoretical Modelmentioning
confidence: 99%